Keteladanan Pelayanan Yesus Menurut Injil Matius dan Penerapannya oleh Guru Sekolah Minggu - Nelly Nelly; Asriani Sri Devi Hulu; Jonar Situmorang (Didache: Journal of Christian Education, 2022)
In the world of education, exemplary is a big responsibility that must be carried out by a teacher in carrying out his duties as a good educator. This is very important because the teacher's example can affect all aspects of the behavior and actions of students. A good teacher can be said to be responsible when he is able to apply good qualities and characters so that students can imitate them. In applying His example, Jesus was present as a professional teacher to set a good example and deserves to be followed by His students and many people. A teacher's attitudes, methods, and actions cannot be properly evaluated unless they are in line with what Jesus taught. The purpose of this article is to develop the attitude and teaching behavior of Sunday School teachers to be like Jesus' example in serving according to the Gospel of Matthew. A qualitative approach is used with a descriptive method. It can be concluded that Jesus is the best example to follow in personality, spirituality, and relationships for the progress of the ministry of GPdI Sunday School teachers Ora Et Labora Majalaya Bandung.